The Effect of Addition NPK on Pineapple Peel Fermentation to Produce Bioethanol as a Premium Extender - Azhis Sholeh Buchori; Susilawati Susilawati (Universitas Sultan Ageng Tirtayasa, 2021)
The depletion of fossil fuels requires alternative energy, one of which alternative energy is bioethanol. Pineapple peel waste has the potential to produce bioethanol because it contains 17.53% carbohydrates and 13.65% sugar which is quite high. The purpose of this study was to produce bioethanol from pineapple peels with the addition of NPK fertilizer as nutrition. The method used is to conduct experiments with the stages: extraction, saccharification, fermentation, distillation, analysis and conclusions. The results obtained were that the highest bioethanol content was obtained in the addition of 20 grams of NPK fertilizer, namely 29.60%.